PERAMALAN PRODUKSI KARET RAKYAT DI KABUPATEN OGAN KOMERING ULU TAHUN 2026 - Martina Dwianti; fifian permatasari (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2022)
This research is aimed to analyze the forecasting of people’s rubber production in Ogan Komering Ulu District in 2026. The research method used for this type of research uses secondary data. The data collected in this study is in the form of time series data, which are people's rubber production data for the past 10 years in Ogan Komering Ulu District which was obtained from the Agriculture Service and the Central Statistics Agency. Processing and data analysis methods for forecasting people’s rubber production in Ogan Komering Ulu District use exponential forecasting analysis. The results showed that the forecasting of rubber production in Ogan Komering Ulu District tended to fluctuate, from 2018 - 2021 people’s rubber production in Ogan Komering Ulu District the rate of growth was positive which showed an increase in folk rubber production, a positive growth rate would be accompanied by an increase in farmers' income. But in the year 2022 - 2026 the growth rate was negative, indicating a decline in people's rubber production. The decline in people’s rubber production can be caused by declining rubber prices, declining rubber prices which also reduce farmers' income. In addition, the decline in folk rubber production is also caused by weather factors, trees experience drought due to drought so that the sap produced from tapping tends to be less.Keyword: exponential, forecasting, rubber production